2010
DOI: 10.1093/fampra/cmq069
|View full text |Cite
|
Sign up to set email alerts
|

Family intervention to control type 2 diabetes: a controlled clinical trial

Abstract: A family intervention for the control of T2DM was associated with a significant reduction in HbA1c when the intervention was provided. Incomplete implementation, low statistical power and potential confounding variables between groups could be some of the main factors that explain the lack of difference between clinics in the 12-month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(118 citation statements)
references
References 26 publications
6
107
1
4
Order By: Relevance
“…In opposite of the previous study, four studies showed not significantly on medication adherence under the family support (12,20,22,23) . It could be correlated with low family participation (20) , understanding of patient and family member roles, and patients' adoption on medication adherence in the long-term period (22) .…”
Section: Self-care Behavior Outcomescontrasting
confidence: 77%
See 4 more Smart Citations
“…In opposite of the previous study, four studies showed not significantly on medication adherence under the family support (12,20,22,23) . It could be correlated with low family participation (20) , understanding of patient and family member roles, and patients' adoption on medication adherence in the long-term period (22) .…”
Section: Self-care Behavior Outcomescontrasting
confidence: 77%
“…This review verified that five studies follow-up the program by using a face-to-face follow-up (12,15,17,(22)(23)(24)33) . Three studies were noticed to follow-up the program by using the telephone method (13,14,25,26,32) .…”
Section: Follow-up Strategiessupporting
confidence: 63%
See 3 more Smart Citations